Looking for Solutions: Gender Differences in Relationship and Parenting Challenges Among Low-Income, Young Parents. - Albritton, Tashuna; Angley, Meghan; Grandelski, Valen; Hansen, Nathan; Kershaw, Trace (Family process, 2014)
The need for parenting and relationship strengthening programs is important among low-income minority parents where the burden of relational and parental stressors contributes to relationship dissolution. We examine these stressors among young parents. Data were collected from four focus groups (N = 35) with young parents. Data were audio-recorded and transcribed. Inductive coding was used to generate themes and codes, and analysis was completed using NVivo. Relationship and parenting challenges, values, and areas of need were the three major themes that emerged. Women's relationship challenges were family interference and unbalanced parenting, and men reported feeling disrespected and having limited finances. Common relationship challenges for women and men were family interference and unbalanced parenting. Both genders valued trust, communication, and honesty in relationships. Areas of need for women and men included: improving communication and understanding the impact of negative relationships on current relationships. Parenting challenges for women were unbalanced parenting, child safety, and feeling unprepared to parent; men reported limited finances. Both genders valued quality time with child to instill family morals. Areas of need for women and men included learning child discipline techniques and increasing knowledge about child development. Finally, women and men have relationship and parenting similarities and differences. Young parents are interested in learning how to improve relationships and co-parent to reduce relationship distress, which could reduce risk behaviors and improve child outcomes.